Chrysin, baicalein and galangin are indirect activators of the human constitutive androstane receptor (CAR) - Carazo Fernández, Alejandro; Smutny, Tomas; Hyrsová, Lucie; Berka, Karel; Pavek, Petr (Toxicology letters, 2015)
The constitutive androstane receptor (CAR) is a crucial transcriptional regulator of key xenobiotic-metabolizing enzymes such as cytochrome P450 CYP3A4, CYP2C9 and CYP2B6. The flavonoids chrysin, baicalein and galangin have been reported to activate CAR and interfere with EGFR signaling. Nevertheless, it is not known if these flavonoids are direct CAR ligands or indirect phenobarbital-like CAR activators via the inhibition of epidermal growth factor receptor (EGFR) signaling. We analyze the interactions of chrysin, galangin and baicalein and its glycoside baicalin with human CAR. We have employed and validated methods that can study direct interaction with the CAR ligand binding pocket. Secondly, we determined if the compounds affect human EGFR signaling and interact with EGFR. Employing a TR-FRET coactivator assay with recombinant CAR or CAR assembly assay, a consistent activation of CAR with flavonoids and phenobarbital was not observed. It was determined, however, that galangin, chrysin, and baicalein may slightly repress EGFR-Tyr1068 autophosphorylation after EGF treatment, phosphorylation of downstream transcription factor ELK1 and stimulate EGFP-CAR nuclear translocation in primary human hepatocytes. These data suggest that flavonoids chrysin, galangin and baicalein are indirect human CAR activators. This study also demonstrates new approach how to test the direct CAR interaction with its ligands.
Keywords: hepatocyty; flavonoidy; buněčné linie; ErbB Receptors; Constitutive androstane receptor; erbB receptory; protein Elk-1 s doménou ets; flavanony; vazebná místa; konstitutivní androstanový receptor; Flavonoids; lidé; Protein Transport; Phenobarbital; Cytochrome P450; receptory cytoplazmatické a nukleární; Cytochrome P-450 CYP2B6; Hepatocytes; Cell Line; transport proteinů; Gene regulation; Constitutive Androstane Receptor; Receptors, Cytoplasmic and Nuclear; cytochrom P450 CYP2B6; ets-Domain Protein Elk-1; Nuclear receptors; Flavanones; fenobarbital; Binding Sites; Humans